2017
DOI: 10.1080/00036846.2017.1332753
|View full text |Cite
|
Sign up to set email alerts
|

What are the top five journals in economics? A new meta-ranking

Abstract: We construct a meta-ranking of 277 economics journals based on 22 different rankings. The ranking incorporates bibliometric measures from four different databases (Web of Science, Scopus, Google Scholar and RePEc). We account for the different scaling of all bibliometric measures by standardizing each ranking score. We run a principal component analysis to assign weights to each ranking. In our metaranking the top five journals are given by:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 82 publications
(41 reference statements)
0
29
0
2
Order By: Relevance
“…Bornmann et al . () reconfirmed the impact of these five journals in economics. In addition, Journal of Financial Economics, the Journal of Finance and the Review of Financial Studies are considered the top three finance journals (http://jfe.rochester.edu/index.htm).…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Bornmann et al . () reconfirmed the impact of these five journals in economics. In addition, Journal of Financial Economics, the Journal of Finance and the Review of Financial Studies are considered the top three finance journals (http://jfe.rochester.edu/index.htm).…”
Section: Introductionmentioning
confidence: 76%
“…Bornmann et al . () constructed a meta‐ranking of 277 economics journals based on 22 different rankings and suggested that the top five journals are Quarterly Journal of Economics, Journal of Financial Economics, Journal of Economic Literature, Journal of Finance and Econometrica . However, by leaving out the JEL as a survey journal and the finance journals from their top 10, they confirmed the perceived top 5 journals (AER, JPE, ECA, QJE and RES) in the economics profession.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations